The gospel and Venda culture : an analysis of factors which hindered or facilitated the acceptance of Christianity by the Vhavenda - Meiring, Piet (Pieter Gerhard Jacobus), 1941- (University of Pretoria, 2013)
Thesis (PhD (Science of Religion and Missiology))--University of Pretoria, 2007.